2004
DOI: 10.1016/s0277-9536(03)00342-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender bias among children in India in their diet and immunisation against disease

Abstract: This paper conducts an econometric analysis of data for a sample of over 4000 children in India, between the ages of 1-2 years of age, with a view to studying two aspects of the neglect of children: their likelihood of being immunised against disease and their likelihood of receiving a nutritious diet. The starting hypothesis, consistent with an universal interest in gender issues, was that girls were more likely to be neglected than boys. The analysis confirmed this hypothesis. In respect of vaccinations, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(165 citation statements)
references
References 23 publications
5
151
2
Order By: Relevance
“…Even when treatment is sought, significantly smaller sums of money are spent on treatment of women than on men [2]. Gender discrimination exists in child feeding, health care, and nutrition status in India [3][4][5][6][7][8][9], and other South Asian countries [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Even when treatment is sought, significantly smaller sums of money are spent on treatment of women than on men [2]. Gender discrimination exists in child feeding, health care, and nutrition status in India [3][4][5][6][7][8][9], and other South Asian countries [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Gender discrimination in immunization coverage has been shown to exist in all states of India (Pande, Yazbeck, 2003;Borooah, 2004). These studies depicted that female children are subjected to gender discrimination and are not getting proper attention regarding immunization.…”
Section: Resultsmentioning
confidence: 99%
“…This was similar to various studies, though most of the studies enrolled children less than 5 years which was not included in our study and among various social factors like educational status of parents, socioeconomic status, gender was also the most important cause for inequity in immunisation status. [14][15][16][17] All the children were going to school, among males 87% were from private school and 13% from government school, among females 89 % were from private school and 11% from government school, there was no significant difference based on type of school, also there were no school drop outs. A Study showed that percentage of school enrolment and school attendance was less among girls as compared to boys and there were many school dropouts.…”
Section: Discussionmentioning
confidence: 99%